Development of special clothing for burn patients - Shaizadanova, Gulnar; Kucharbaeva, Kaldygul; Abilkalamova, Kamilya; Baizhanova, Zhazira; Sabitova, Alima (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the study is special clothing for burn patients. The insufficiency of the range of special general-purpose clothing significantly reduces the possibilities of using medical technologies, slows down the provision of medical care, reduces the quality of life of patients in the treatment period. Consideration of protective functions and a functional and constructive approach to the development of special clothing for burn patients are important, given that such clothing should protect the patient from infections and facilitate medical procedures by medical personnel. As a result of the study, a set of special general-purpose clothing for burn patients was developed from the medical fabric «Panacea PP 180» with the antibacterial finish CleanOK, taking into account the requirements of functionality, specific features of medical procedures. The features of designing special clothing for patients with thermal skin lesions proposed in this study create more comfortable conditions for the patient compared to standard hospital clothing. The use of mesh fabric in the side parts ensures compliance with hygienic requirements for clothing that form the microclimate of the under-bed space; taking into account the peculiarities of medical procedures and the topography of their implementation, the development of functional and constructive solutions for a set of special clothing is effective. The practical significance of special clothing for burn patients lies in its protective function against infections, the effectiveness of the rehabilitation effect on the body of a sick person, as well as improving the quality of medical procedures performed by personnel in stationary conditions